2020
DOI: 10.1097/bpo.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation for the Treatment of Symptomatic Osteochondritis Dissecans of the Femoral Head in Patients With Sequelae of Legg-Calvé-Perthes Disease

Abstract: Level IV-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…11 Therefore, we suggest that greater OCDs should be treated with reattachment of the fragment through surgical hip dislocation and internal fixation. Lamplot et al 29 have reported predictable x-ray healing and significant clinical improvement following open reduction and internal fixation at mean follow-up of 4.6 years in a series of 7 patients with osteochondritis dissecans with underlying Perthes disease.…”
Section: Discussionmentioning
confidence: 98%
“…11 Therefore, we suggest that greater OCDs should be treated with reattachment of the fragment through surgical hip dislocation and internal fixation. Lamplot et al 29 have reported predictable x-ray healing and significant clinical improvement following open reduction and internal fixation at mean follow-up of 4.6 years in a series of 7 patients with osteochondritis dissecans with underlying Perthes disease.…”
Section: Discussionmentioning
confidence: 98%
“…Lamplot et al, 9 in a study of 64 patients treated with hip preservation surgery for LCPD, reported that the 7 patients (7 hips) who underwent surgical hip dislocation and ORIF of femoral head OCD had significant improvement in internal rotation in flexion at final follow-up. The authors observed radiographic healing without evidence of implant failure and no progression of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondritis Dissecans (OCD) of the femoral head has been reported in 2% to 7% of patients diagnosed with LCP disease. 9 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, although this study furthers our understanding of the revascularization process in LCPD, at this time we cannot offer clinical guidance based on the results of this study. One area in which the ligamentum teres may be jeopardized during surgery is through techniques in hip preservation, specifically with surgical hip dislocation, which is increasingly utilized in management of hip deformity related to LCPD 12–17. However, the safe surgical hip dislocation approach, which may involve transection of the ligamentum teres and disruption of the ligamentum teres vessels, is generally performed in the healed stage of LCPD after which time the perfusion from the ligamentum teres vasculature has again subsided in favor of the MFCA vessels 4,5…”
Section: Discussionmentioning
confidence: 99%
“…One area in which the ligamentum teres may be jeopardized during surgery is through techniques in hip preservation, specifically with surgical hip dislocation, which is increasingly utilized in management of hip deformity related to LCPD. [12][13][14][15][16][17] However, the safe surgical hip dislocation approach, which may involve transection of the ligamentum teres and disruption of the ligamentum teres vessels, is generally performed in the healed stage of LCPD after which time the perfusion from the ligamentum teres vasculature has again subsided in favor of the MFCA vessels. 4,5 In conclusion, this study provides further evidence of the role of the artery of ligamentum teres in the revascularization of the femoral head in the early stages (Waldenström I to IIa) of LCPD.…”
Section: Discussionmentioning
confidence: 99%